A aplicação do regulamento de aquisições do BIRD frente à Constituição Federal e aos princípios licitatórios brasileiros - Acioly Filho, Antônio Carlos (2021)
This research paper provides the operation of the IBRD acquisition regulations system under the Constitution of the Federative Republic of Brazil and under the brazilian bidding principles. Thus, it seeks to contextualize the legal system related to the bidding process, especially regarding to applicable principles, with the rules that applies to the international bidding process. The specific research problem corresponds to verify how the brazilian national legislation is designed to resolve conflicts between brazilian national laws and international regulatory laws especially created by the World Bank. The research hypothesis is the analysis of the compatibility of material sources between international bidding legal system and the precepts contained in article 37, XXI, of the Brazilian Federal Constitution. If they are compatible, the brazilian bidding legal system may be lifted. If not, international bidding regulations should not be applied, since they conflict with the Federal Constitution of Brazil.The objective of this research is to determine the constitutionality of the bidding rules of IBRD confronted with the principles contained in the Federal Constitution of Brazil. Therefore, a broad study of the national bidding system, international bidding under the focus of the World Bank, the principles of IBRD and of the supremacy from the Federal Constitution is conducted, while the Consittution emerges ans the guiding diploma of the brazilian national bidding process. This is a bibliographic research, based on secondary published materials sources related to the subject matter of analysis, such as books, specialized journals in law, scientific articles, encyclopedias, monographs, theses, dissertations, normative provisions and jurisprudence. From a methodological point of view, the qualitative criterion is used, considering the subjectivity of the research based on opinions of scientists in the legal field. The method, in turn, is inductive, taking the base of general information, applicable to other cases of the same matter.